PERUBAHAN PRILAKU MASYARAKAT TERHADAP POLA RUANG BANGUNAN PURA DESA, DESA JERO KUTA BATUBULAN - PUTRI AYU DEVY PERMATA SARI; NI KOMANG INDRA MAHAYANI; PUTU SISKHA PRADNYANINGRUM (Universitas Mahasaraswati K. Mataram, 2024)
Pura Desa, located in Jero Kuta Village, Batubulan District, Gianyar Regency, is one of the preserved temples, and its original structure can still be seen both from the building and the carvings used. However, although many aspects have been preserved, the spatial layout of the Village Temple in Jero Village, Kuta Batubulan has changed. This research aims to determine the impact of changes in community behavior on the transformation of temple layout in Jero Village, Kuta Batubulan. Qualitative research methods were used to understand in depth how changes in behavior of the Jero Kuta Village community influenced the transformation of the Village Temple spatial layout, both its impact on social interactions, religious practices and the cultural identity of the local community. By understanding the influence of community behavior on temple layout, this research provides valuable insights for decision makers and stakeholders. The practical implications can help in designing policies that support the preservation of local cultural values while balancing ongoing traditions and changes in behavior of the people of Jero Kuta Batubulan Village in response to modern developments